Bonding Performance of Simplified Adhesive Systems in Noncarious Cervical Lesions at 2-year Follow-up: A Double-blind Randomized Clinical Trial - Zanatta, R. F.; Silva, T. M. [UNESP]; Esper, M. A. L. R. [UNESP]; Bresciani, E. [UNESP]; Goncalves, S. E. P. [UNESP]; Caneppele, T. M. F. [UNESP] (Operative Dentistry Inc, 2019)
Objectives: This study aimed to evaluate the bonding performance of a universal adhesive used according to self-etching or etch-and-rinse protocols in noncarious cervical lesions (NCCLs) and to compare the two protocols with their respective gold standard techniques. Methods and Materials: This randomized, double-blind clinical study enrolled 34 participants who met the inclusion criteria, 29 of whom returned after two years. They received 152 restorations bonded with one of the three adhesives (Scotchbond Universal Adhesive, Adper Single Bond 2, or Clearfil SE Bond) and one of the two bonding techniques tested. The NCCLs were restored with nanocomposite resin (Filtek Supreme). Final contours were done with a fine diamond rotary instrument and polished with rubber points. The restorations were evaluated using the FDI World Dental Federation criteria at baseline (seven ) days after the restoration procedure), 6, 12, and 24 months. Descriptive statistics, Kruskal-Wallis, Friedman analysis of variance, and least significant difference tests were performed. Results: No statistically significant differences were found in esthetics or the functional and biological evaluated criteria among the adhesive systems and techniques. Conclusions: The Scotchbond Universal system behaved similarly to the conventional etch-and-rinse or self-etching systems in all the adhesion strategies in the evaluated periods.